Dylematy wyceny wartości niematerialnych i prawnych w zakładach opieki zdrowotnej - Dotkuś, Waldemar (The Dilemmas of Pricing Immaterial and Legal Values in Institutions of Wholesome Healthcare, 2005)
The continuation of company's existence is caused by the owner's will and special conditions, which the healthcare institutions act in. Financial statement being the basis on which managers are assessed, should be clear and reliable financial situation. One of foundations considered while taking down the balance is that it the premises in the subject functions, make the basis to claim that the continuation of working will not be stopped. On this basis a problem emerges connected with pricing intangible assets that belongs to healthcare institution. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 79-84